Development of a data compression method by merging data blocks - Bouhafs ,Rokia; Bouzidi,Abir (Université of Eloued جامعة الوادي, 2026)
"شهد العالم الرقمي نموًا هائلًا في حجم البيانات، مما أدى إلى الحاجة إلى تقنيات فعّالة لتخزين المعلومات ونقلها. ونظرًا لمحدودية الموارد، تم اقتراح تقنيات ضغط البيانات لتقليل حجم البيانات المخزنة أو المنقولة. إذ تساهم مفاهيم ضغط البيانات في تحسين استغلال مساحة التخزين وعرض النطاق الترددي للاتصال، الأمر الذي أدى إلى تطوير العديد من الأساليب من زوايا متعددة. يركز هذا العمل على تنفيذ طريقة ضغط بيانات من نوع بدون فقدان تعتمد على دمج كتل البيانات بهدف تحسين نسبة الضغط. تقوم الطريقة بدمج محتوى كتلتين من البيانات لتحقيق نسبة ضغط أفضل. تم اختبار النهج المقترح على مجموعة بيانات هي: Prague Corpus، والتي تتضمن أنواع من الملفات مثل قواعد البيانات، نصوص البرمجيات، والصور الطبية. أظهرت النتائج تحسنًا جيدًا في نسب الضغط على مستوى الكتل، لكنها سجلت قيمًا سلبية على مستوى الملفات، مما يُبرز الحاجة إلى خوارزميات معالجة أولية قبل تنفيذ عملية الدمج. تفتح هذه الدراسة آفاقًا جديدة لتحسين ضغط البيانات في التطبيقات العملية، مع إمكانية التوسع في استخدام تقنيات الذكاء الاصطناعي لتحقيق نسب ضغط أعلى في المستقبل""The digital world has witnessed a massive growth in data volume, creating a need for efficient techniques for storing and transmitting information. Due to limited resources, data compression techniques have been proposed to reduce the amount of data stored or transmitted. Data compression concepts contribute to the optimization of storage space and communication bandwidth, which has led to the development of numerous approaches from various perspectives. This work focuses on the implementation of a lossless data compression method based on data block merging to improve compression ratios. The method merges the contents of two data blocks to achieve a better compression ratio. The proposed approach was tested on the Prague Corpus dataset, which includes various file types such as databases, software scripts, and medical images. The results showed significant improvements in compression ratios at the block level, but recorded negative values at the file level, highlighting the need for preprocessing algorithms before implementing the merging process. This study opens new avenues for improving data compression in practical applications, with the potential to expand the use of artificial intelligence techniques to achieve higher compression ratios in the future."
مذكرة تخرج سنة ثالثة ليسانس إعلام آلي
Keywords: الكلمات المفتاحية : ضغط البيانات، تقليل التكرار، خوارزميات الضغط، مجموعات بيانات الضغط.; Keywords: Data compression; Redundancy reduction; Compression algorithms; Compression datasets